Organocatalytic [4+1]-annulation approach for the synthesis of densely functionalized pyrazolidine carboxylates - Lalwani, Komal G.; Aher, Ravindra D.; Sudalai, Arumugam (RSC Advances, 2015)
A novel one-pot [4+1]-annulation process for the asymmetric synthesis of densely functionalized pyrazolidine carboxylates is described. The in situ generated gamma-hydrazino-alpha,beta-unsaturated ester obtained via proline catalysis acts as a four-atom component, and Corey's sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrazolidine carboxylate units in a highly enantio- and diastereoselective fashion.